Evaluation of antioxidant activity of grapevine leaves extracts (Vitis labrusca) in liver of Wistar rats - THAYS K. SCHAFFER (Anais da Academia Brasileira de Ciências, 2016)
The aim of this study was to evaluate the hepatoprotection of organic and conventional grapevine leaves extract ( Vitis labrusca ). The total polyphenol content and the isolate polyphenols by HPLC were evaluate. The animals received intraperitoneal injections of saline or extracts (conventional or organic - 30 mg/kg) for 14 days. On day 15, the rats received carbon tetrachloride (CCl 4 ) or mineral oil (i.p.). After 4h, the animals were euthanized. The analysis of the liver enzymes activity (AST, ALT, GGT) was performed using serum, obtained by blood and the levels of lipid peroxidation (TBARS), protein oxidation (carbonyl), and the activity of antioxidant enzymes superoxide dismutase and catalase were analyzed in the liver. The results showed that the organic extract is richer in polyphenol and resveratrol than the conventional one. Both extracts prevent lipid peroxidation and protein oxidation generated by CCl 4 . Moreover, the extracts demonstrated ability to modulate the activity of SOD and CAT, as well as to establish a balance in the ratio of SOD/CAT. We also found that the CCl 4 increased the levels of AST and GGT, and that both extracts prevent this. These results indicate that grapevine leaves extracts, both, organic and conventional, can prevent liver disorders.